Spectrum of lymphomas across different drug treatment groups in rheumatoid arthritis: a European registries collaborative project - Mercer, Louise K; Regierer, Anne C; Mariette, Xavier; Dixon, William G; Baecklund, Eva; Hellgren, Karin; Dreyer, Lene; Hetland, Merete Lund; Cordtz, René; Hyrich, Kimme; Strangfeld, Anja; Zink, Angela; et al. (Annals of the rheumatic diseases, 2017)
BACKGROUND: Lymphomas comprise a heterogeneous group of malignant diseases with highly variable prognosis. Rheumatoid arthritis (RA) is associated with a twofold increased risk of both Hodgkin's lymphoma (HL) and non-Hodgkin's lymphoma (NHL). It is unknown whether treatment with biologic disease-modifying antirheumatic drugs (bDMARDs) affect the risk of specific lymphoma subtypes. METHODS: Patients never exposed to (bionaïve) or ever treated with bDMARDs from 12 European biologic registers were followed prospectively for the occurrence of first ever histologically confirmed lymphoma. Patients were considered exposed to a bDMARD after having received the first dose. Lymphomas were attributed to the most recently received bDMARD. RESULTS: Among 124 997 patients (mean age 59 years; 73.7% female), 533 lymphomas were reported. Of these, 9.5% were HL, 83.8% B-cell NHL and 6.8% T-cell NHL. No cases of hepatosplenic T-cell lymphoma were observed. Diffuse large B-cell lymphoma (DLBCL) was the most frequent B-cell NHL subtype (55.8% of all B-cell NHLs). The subtype distributions were similar between bionaïve patients and those treated with tumour necrosis factor inhibitors (TNFi). For other bDMARDs, the numbers of cases were too small to draw any conclusions. Patients with RA developed more DLBCLs and less chronic lymphocytic leukaemia compared with the general population. CONCLUSION: This large collaborative analysis of European registries has successfully collated subtype information on 533 lymphomas. While the subtype distribution differs between RA and the general population, there was no evidence of any modification of the distribution of lymphoma subtypes in patients with RA treated with TNFi compared with bionaïve patients.
Keywords: DMARDs(biologic); anti-TNF; Lymphoma, T-Cell; Europe; Evropa; Middle Aged; registrace; mužské pohlaví; epidemiology; Registries; lymfom; ženské pohlaví; Humans; antirevmatika; B-buněčný lymfom; Arthritis, Rheumatoid; lidé středního věku; inhibitory TNF; Tumor Necrosis Factor Inhibitors; rizikové faktory; lymfom T-buněčný; revmatoidní artritida; Antirheumatic Agents; nehodgkinský lymfom; Lymphoma, B-Cell; Lymphoma, Non-Hodgkin; rheumatoid arthritis; Female; Risk Factors; lidé; Male; Lymphoma